The Role of Competitive Strategy and Green Supply Chain Management in MSME Performance - Suwandi, Suwandi; Badrianto, Yuan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study investigates the role of competitive strategy and green supply chain management (GSCM) in the performance of Micro, Small and Medium Enterprises (MSMEs) in West Java. Using a sample of 87 MSMEs, data was collected through questionnaires distributed to various MSMEs in the West Java region, using a Likert scale for response evaluation. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) through the Smart PLS program.The results of this study indicate that both competitive strategy and GSCM have a significant influence on MSME performance. Competitive strategy, which includes product differentiation, cost leadership, and market focus, has improved the operational efficiency, market responsiveness, and competitive advantage of MSMEs. Meanwhile, the implementation of GSCM, which emphasizes environmentally friendly operations and sustainable resource management, not only improves compliance with environmental regulations but also strengthens the reputation and legitimacy of MSMEs in the eyes of stakeholders and consumers. These findings confirm the importance of adopting and integrating innovative and sustainable business practices to improve MSME performance. Consequently, this study suggests the need for more strategic policy interventions and support for MSMEs to develop their capacity in competitive strategy and GSCM, thereby strengthening their position in the market and their contribution to the regional economy and environmental sustainability